2019
DOI: 10.1136/jim-2018-000801
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomogram based on SIRI for predicting the clinical outcome in patients with nasopharyngeal carcinomas

Abstract: The Systemic Inflammation Response Index (SIRI), based on peripheral lymphocyte, neutrophil, and monocyte counts, was recently investigated as a prognostic marker for several tumors. However, use of the SIRI has not been reported for nasopharyngeal carcinoma (NPC). We evaluated the prognostic value of the SIRI in primary and validation cohorts. We also established an effective prognostic nomogram for NPC based on clinicopathological parameters and the SIRI. The predictive accuracy and discriminative ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 28 publications
5
61
0
Order By: Relevance
“…A limited number of studies have been published analyzing the prognostic capacity of SIRI. [27][28][29][30][31] To the best of our knowledge, this is the first study analyzing SIRI as a prognostic factor in a large series of OSCC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A limited number of studies have been published analyzing the prognostic capacity of SIRI. [27][28][29][30][31] To the best of our knowledge, this is the first study analyzing SIRI as a prognostic factor in a large series of OSCC.…”
Section: Discussionmentioning
confidence: 91%
“…We agree with Qi et al that incorporating the prognostic value added by each leukocyte count creates an even more integrative biomarker than analyzing the individual counts. A limited number of studies have been published analyzing the prognostic capacity of SIRI . To the best of our knowledge, this is the first study analyzing SIRI as a prognostic factor in a large series of OSCC.…”
Section: Discussionmentioning
confidence: 96%
“…In a cohort of 285 patients with nasopharyngeal carcinoma, Chen et al found a significant correlation between SIRI and OS. Using ROC curves, they were able to show how the AUC obtained with SIRI was superior to the AUC of other parameters such as NLR or LMR.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Chen et al found that SIRI was significantly associated with overall survival (OS) in patients with nasopharyngeal carcinoma, acting as a biomarker with independent prognostic capacity. To the best of our knowledge, there are no studies analyzing the prognostic capacity of SIRI in patients with HNSCC in sites other than the nasopharynx.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, immune cell-related indices such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-tomonocyte ratio (LMR) have been used to predict prognosis and recurrence in various malignancies [2]. In recent years, a novel inflammatory marker, the systemic inflammation response index (SIRI), which is calculated using the levels of neutrophils, monocytes, and lymphocytes, has shown an ability to predict prognosis in pancreatic cancer [3], gastric cancer [4], and nasopharyngeal cancer [5].…”
Section: Introductionmentioning
confidence: 99%